Keanekaragaman Jenis Kantong Semar (Nepenthes spp) di KHDTK Hutan Pendidikan Hampangen Universitas Palangka Raya: The Diversity of Kantong Semar (Nepenthes spp) in Hampangen Educational Forest KHDTK, University of Palangka Raya - Patricia Erosa Putir; Eritha Kristiana Firdara; Nuwa Nuwa; Andreas J.F.S. (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2022)
The purpose of this study was to identify the species and determine the diversity of Nepenthes spp in the KHDTK Hampagen Educational Forest, University of Palangka Raya. Determination of observations using purposive sampling method by making six lanes with a length of 100 m, which are then divided into 10 (ten) plots with a size of 10 m x 10 m in each of these lanes. Result of research showed  that four  Kantong Semar i.e:  Nepenthes rafflesiana Jack, Nepenthes mirabillis (Lour.) Druce, Nepenthes gracillis Korth, and Nepenthes reinwardtiana Miq. The most dominant species was Nepenthes reinwardtiana Miq with value (INP=62.5863%) followed by Nepenthes mirabillis (Lour.) with (INP=50.1568%), Nepenthes rafflesiana Jack with (INP=48.8233) and the lowest species Nepenthes gracillis Korth with (INP=38.4245%). The highest diversity index of Nepenthes  reinwardtiana Miq. (H'=0.37), followed by Nephentes  rafflesiana Jack and Nephentes  mirabilis (Lour.) Druce with the same diversity index (H'= 0.34) while the lowest diversity index was for Nephentes gracilis Korth (H'= 0.33). The highest abundance value of Nepenthes reinwardtiana Miq was found for species abundance (e=0.26) and the lowest abundance was found for Nepenthes gracilis Korth (e=0.23).